ANALISA GANGGUAN SUTM 20 KV PENYULANG SENGGIRING 3 DI PT. PLN (PERSERO) AREA PONTIANAK - Asnawi . (Faculty of Engineering, Universitas Tanjungpura, 2018)
This research is to observe the problem that happen in Medium Voltage Air Duct or known as Saluran Udara Tegangan Menengah (SUTM) 20 KV feeder Senggiring 3 in PT. PLN (Persero) Area Pontianak. Feeder Senggiring 3 is a feeder that often to have many disturbances occur and also die out. The length of the feeder Senggiring 3 sistem as far as 145,3 Km in Kabupaten Mempawah and 398,5 Km in Kabupatan Ngabang. In totally the length of feeder Senggiring 3 sistem is 443,8 Km. Total of distribution substation in feeder Senggiring 3 is 220 substation. Feeder Senggiring 3 use HIC (High Insulation Conductor) type for the section and AAAC (All Aluminium Alloy Conductor) with 70 mm2 and 150 mm2 for the diameter. The disturbances that often happen in feeder Senggiring 3 is fases short connection and 1 ground fase. The persentation the cause of the disturbances in feeder Senggiring 3 are 51% because of tree, 26% because of weather/nature factor, 12% because of the animal, 10%because of kite, and 1% because of the construction. The calculation method that used is calculated Impedansi and flow short disturbances connection. After doing some analysis, there is some ways to resolve the disturbances in feeder Senggiring 3, among others are sistem maintenance with cutting down the tree that stick to the sistem with a safe distance, cleaning all along the feeder Senggiring 3 sistem from the wire kite and kite framework, changes the protection tools that not working as usual and doing the socialisation to the community about the dangerous of electricity also the impact of the die out because of that disturbances factor. The result from the repairing from June 2016 until July 2017 is decreasing the persentation as much as 80,7%. So in conclusion, that the act that have to do to prevent the disturbances to be happen in feeder Senggiring 3 is to change the tools that already not working as usual anymore, like protection tools, nd have routine maintenance in feeder Senggiring 3. Keyword : Disturbances Of Feeder, Maintenance The Sistem, Continuity Of Electric